2008
DOI: 10.1055/s-2008-1046759
|View full text |Cite
|
Sign up to set email alerts
|

High Omega-3 Fat Intake Improves Insulin Sensitivity and Reduces CRP and IL6, but does not Affect Other Endocrine Axes in Healthy Older Adults

Abstract: Aging diminishes hormone secretion and target cell responsiveness, possibly due to loss of cell membrane fluidity or alteration of membrane phospholipids affecting signal transduction. We investigated whether a high omega-3 polyunsaturated fatty acid diet would improve endocrine function in 6 men and 6 women aged over 60 years. Subjects first ate an isocaloric control diet for 6 weeks, followed by an 8-week experimental diet, which included 720 g of fatty fish weekly plus 15 ml of sardine oil daily. In the las… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
88
1
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(95 citation statements)
references
References 63 publications
5
88
1
1
Order By: Relevance
“…Other factors, such as changes in body weight, insulin sensitivity, saturated fat and energy intake, could also have affected the decreases observed in inflammatory and endothelial markers after the dietary interventions [37,[42][43][44][45]. However, in multivariate analyses taking into account the minor changes in BMI or the recorded saturated fat or energy intakes during the study the results were not altered with respect to E-selectin and hsCRP.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Other factors, such as changes in body weight, insulin sensitivity, saturated fat and energy intake, could also have affected the decreases observed in inflammatory and endothelial markers after the dietary interventions [37,[42][43][44][45]. However, in multivariate analyses taking into account the minor changes in BMI or the recorded saturated fat or energy intakes during the study the results were not altered with respect to E-selectin and hsCRP.…”
Section: Discussionmentioning
confidence: 94%
“…A Mediterranean-style diet, in which whole grains and fibre are highly consumed, has been shown to ameliorate circulating levels of CRP and to reduce the risk of type 2 diabetes mellitus [35,36]. Fish intake and n-3 fatty acids have been shown to decrease CRP levels [37], albeit not in all studies [38,39]. Based on our study design, we hypothesised that there would be a greater decrease in this inflammatory marker with the Healthy Diet than with the WGED.…”
Section: Discussionmentioning
confidence: 98%
“…The febrile and TNF-a response to LPS challenge was also attenuated in pigs that were supplemented with n-3 FA in their diet (Gabler et al, 2008). Although no reports of n-3 FA-mediated changes in blood Hp concentration can be found in the literature, a human study recently documented that high n-3 FA intake reduced C-reactive protein, another important positive hepatic APP of humans (Tsitouras et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Lowering the N-6 to N-3 ratio is hypothesized to reduce the risk of colorectal cancer, because N-3 fatty acids inhibit the production of proinflammatory, N-6-derived eicosanoids via the cyclooxygenase-2 enzyme (17,18,20,24). Prospective studies and relatively shortterm clinical trials have shown that N-3 fatty acids, particularly the long-chain or marine fatty acids (DHA and EPA), decrease both biomarkers of inflammation (25)(26)(27) and rectal cell proliferation (7,(10)(11)(12)(13). Such evidence, coupled with the efficacy of nonsteroidal anti-inflammatory drug (NSAID), strong cyclooxygenase inhibitors, to reduce the risk of colorectal neoplasia (28)(29)(30)(31), supports the promise for marine N-3 PUFAs in the prevention of colorectal cancer through modulation of similar mechanisms.…”
Section: Introductionmentioning
confidence: 99%